Pengaruh Arus Kas, Laba, Arus Kas Investasi, Arus Kas Operasi dan Arus Kas Pendanaan (Literature Review Manajemen Keuangan) - Nova Lia Situmorang; Ramadhani Nurfitria; Nehemia Apriyani Panjaitan; Cantika Ramadina PD; Tri Yulaeli (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
An investor in investing always expects high stock returns. Therefore, investors must be able to assess which companies have good performance. Stock returns are a matter of great concern to investors considering the level of profit that investors will enjoy from their investments. Financial reports, especially those related to information on changes in cash flows, accounting profit, investment cash flows, funding flows and operating cash flows are important information that investors can use to assess company performance. This study aims to determine whether the information for investors to make investment decisions is reflected in the stock returns to be obtained. This study is also intended to determine which performance measures have the most significant influence on stock returns. Information that is often used by investors in considering investment decisions in increasing stock returns is net income, cash flow, funding and operating cash flow. Writing this article aims to build a hypothesis of the influence between variables to be used in further research. This article discusses the effect of stocks on cash flow, accounting profit, operating cash flow, investment cash flow and funding cash flow, an introductory literature study on financial management.